2022
DOI: 10.1126/science.abm1472
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the melting curve of iron at super-Earth core conditions

Abstract: Terapascal iron-melting temperature The pressure and temperature conditions at which iron melts are important for terrestrial planets because they determine the size of the liquid metal core, an important factor for understanding the potential for generating a radiation-shielding magnetic field. Kraus et al . used laser-driven shock to determine the iron-melt curve up to a pressure of 1000 gigapascals (see the Perspective by Zhang and Lin). This value is about thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 72 publications
4
30
0
Order By: Relevance
“…Combining eqn (14) and (15) yieldswhereNext, to minimize the number of empirical inputs for WHEP calculations, we constrain T 1 ( P 1 ) and T 2 ( P 2 ) by T 1 ( P 1 ) = T m (0),Interestingly, the initial melting gradient can be linked to the bulk modulus via the Lindemann criterion as 58 Entering eqn (20)–(22) into eqn (18) provides us with the final expression for the melting profile asUnlike eqn (17) and (23) only requires empirical information about the zero-pressure melting temperature T m (0). To verify the reliability and flexibility of eqn (23), we perform numerical calculations for tantalum, 59–62 iron, 63–66 and magnesium oxide 67–70 because their melting behaviors have been thoroughly measured by modern DAC and SW methods. As presented in Section II and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combining eqn (14) and (15) yieldswhereNext, to minimize the number of empirical inputs for WHEP calculations, we constrain T 1 ( P 1 ) and T 2 ( P 2 ) by T 1 ( P 1 ) = T m (0),Interestingly, the initial melting gradient can be linked to the bulk modulus via the Lindemann criterion as 58 Entering eqn (20)–(22) into eqn (18) provides us with the final expression for the melting profile asUnlike eqn (17) and (23) only requires empirical information about the zero-pressure melting temperature T m (0). To verify the reliability and flexibility of eqn (23), we perform numerical calculations for tantalum, 59–62 iron, 63–66 and magnesium oxide 67–70 because their melting behaviors have been thoroughly measured by modern DAC and SW methods. As presented in Section II and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We note that, although the Jian et al. model is nominally designed for ambient-pressure conditions, we have found that, when coupled with an appropriate equation of state, it is possible to adjust the single empirical fitting parameter ξ in their model to yield reasonable results for solid–liquid interfaces in water/ice VII, , gallium, and iron at high-pressure conditions. The new model that we present in this work, while it is still largely phenomenological in nature like the others we have discussed, is nevertheless expected to provide a more realistic representation of the underlying behavior at high pressures.…”
Section: Methodsmentioning
confidence: 95%
“…For example, measurements of the dissipated thermal energy by means of infrared detection have been found to be rather sensitive to the calibration procedure, with updates to this procedure able to change the apparent TQC by as much as a factor of two [9]. During material tests performed at most extreme deformation rates, e.g., at the National Ignition Facility [10,11], uncertainty in specimen temperature can reach hundreds of Kelvin making extraction of the material's intrinsic thermo-mechanical properties quite difficult. Despite (or perhaps due to) our continually expanding and improving experimental capabilities, the range of TQC values appearing in the literature is not narrowing, and if anything has expanded to the entire interval between 0.1 and 1.0.…”
Section: Introductionmentioning
confidence: 99%